INFLUENCE OF EXTRACT AND PHENOL GLYCOSIDES FROM ROSE PETALS ON THE FIBRILS OF AMYLOID PEPTIDE Aβ(1-42). STUDY BY TRANSMISSION ELECTRON MICROSCOPЕ (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The analyses of conformational diversity of Aβ(1-42) peptide aggregates by transmission electron microscope (TEM) visualization evidenced the simultaneous presence of non mature small protofibrils, mature fibrils and ribbon-like structural forms. In the presence of extract and phenol glycosides from rose petals, the deformations of aggregates and the amorphous bundles without clear structure were registered. The observations are in line with the ability of plant preparations to hinder the aggregation of Aβ(1-42) and to disaggregate the preformed aggregates. The work manifested that TEM is a reasonable approach in seeking effective agents for treatment of amyloid diseases and evaluating plant medicines as such agents.
Keywords: amyloid beta 1-42 peptide, transmission electron microscopy, amyloidosis, plant preparations